Induction of Nonspecific Resistance by Endotoxin in Unresponsive Mice - Margherita, S. S. (1965)
Margherita, S. S. (Temple University School of Medicine, Philadelphia, Pa.), and H. Friedmann. Induction of nonspecific resistance by endotoxin in unresponsive mice. J. Bacteriol. 89:277–280. 1965.—Serratia marcescens endotoxin was tested for protective effect in animals of varying immunological competence. A quantity of endotoxin capable of inducing resistance in mice to a standardized challenge of Diplococcus pneumoniae was equally effective in animals immunologically paralyzed with a high dose of homologous pneumococcal polysaccharide. Failure of the unresponsive state to influence the degree of resistance induced by endotoxin suggests that a specific humoral factor does not play a significant role in the nonspecific resistance.